Improving Reading Comprehension of Tenth Grade Students of SMA Negeri 1 Sojol Using Read-Cover-Remember-Retell (RCRR) Strategy - Nur’Ainun, Nur’Ainun; Syahrul Munir; Wahyudin, Wahyudin; Darmawan, Darmawan (Universitas Cokroaminoto Palopo, 2024)
The research aims to find out whether or not the use Read-Cover-Remember-Retell (RCRR) can improve students’ reading comprehension of the tenth grade students of SMA Negeri 1 Sojol. The researcher used quasi-experimental research design which involved two groups namely experimental group and control group. The population was 166 students in grade tenth. The samples were 67 students, selected by using the purposive sampling technique. The instrument of collecting the data was test. The test consisted of pre-test and post-test. The data were analyzed statistically using, 0.05 level of significance and 60 degree of freedom. Based on the data analysis, it was founds that the students’ mean score of experimental groups post-test was 64.38 greater than the control groups mean score, 47.12. Comparison the two tests of scale describes that value = 10.18> value = 1.659 which indicates that the research hypothesis is accepted. In other words, the reading comprehension of the tenth grade students of SMA Negeri 1 Sojol can be improved by using the ReadCover-Remember-Retell (RCRR) Strategy